Paradigm of integrative OMICS of microbial technology towards biorefinery prospects - Jacob, Samuel; Rajeswari, Gunasekaran; Rai, Awantika; Tripathy, Sushree Shweta; Gopal, Swathy; Das, Eeshita; Kumar, Vinod; Jeevan Kumar, S. P.; Aminabhavi, Tejraj M.; Garlapati, Vijay Kumar (Elsevier, 2024)
Climate change, finite natural resources, and increasing population necessitate producing sustainable energy with positive economic growth. Recent advances in OMICS coupled with genome editing and synthetic biology have paved the way for the development of sustainable technologies. These techniques help identify critical genes/pathways and re-construct and redesign biological pathways to develop eco-friendly and economically viable industrial metabolites. With the help of microbial technology, biorefinery-related research is actively pursued in many countries to develop microbial strains, producing varied value-added biochemicals and biofuels. The application of multi-omics data in deciphering key genes, their manipulation, and outcomes implies the domain's potential to find new horizons in biorefineries using microbial factories to produce various biofuels and biorefinery products. This review illustrates OMICS role in developing industrial chemicals and microbial biorefineries. Besides, prospects for genome editing and synthetic biology have been elucidated.
Keywords: biorefinery; metabolic engineering; Microbial technology; Multi-omics; Synthetic biology